On the Use of Panel Stationarity Tests in Convergence Analysis: Empirical Evidence for the EU Countries - Mariusz Prochniak; Bartosz Witkowski (Institute of Economic Research (IER), 2015)
The study examines the concept of stochastic convergence in the EU28 countries over the 1994-2013 period. The convergence of individual countries' GDP per capita toward the EU28 average per capita income level and the pair-wise convergence between the GDP of individual countries both are analyzed. Additionally, we introduce our own concept of conditional stochastic convergence which is based on adjusted GDP per capita series in order to account for the impact of other growth factors on GDP. The analysis is based on time series techniques. To assess stationarity, ADF tests are used. The study shows that the process of stochastic convergence in the EU countries is not so widespread as the cross-sectional studies on ? or ? convergence indicate. Even if we extend the analysis to examine conditional stochastic convergence, the number of converging economies or pairs of countries rises but not as much as it could be expected from the cross-sectional studies.
Keywords: C22; C23; O47; O52; 330; economic growth; convergence; catching up; stationarity; ADF test